Fabrication of cutting inserts with chromium-molybdenum steel for turning operations using material extrusion technology. - Rodríguez Alabanda, Óscar; Guerrero-Vacas, Guillermo Rafael; Martín-Sánchez, María Jesús; Martín-Fernández, Francisco de Sales (Elsevier, 2024)
In this study, cutting inserts for turning were produced using metal 3D printing’s material extrusion technology. The primary focus was on optimizing cutting parameters. An experimental plan was devised involving rounds of cutting tests based on a design of experiments and analysis of variance. Inserts were manufactured by printing bound metal powder filament, a combination of chromium-molybdenum tool steel with a polymeric binder. After printing, green parts underwent debinding to eliminate the binder, eventually resulting in full metal parts via sintering. These inserts underwent machining tests on aluminum-copper EN AW-2030 alloy specimens. Results indicated that the inserts could function within cutting speeds (Vc) ranging from 40 to 260 m/min, feed rates (f) from 0.05 to 0.25 mm/r, and radial pass depths (ap) from 0.1 to 2.4 mm. Optimal technological conditions were determined as Vc = 160–200 m/min, f = 0.20–0.25 mm/r, and ap = 1.2 mm. Analysis revealed that cutting speed was less significant than feed rate or depth of cut on tool wear. Feed rate minimized wear within the 0.15–0.25 mm/r range, while pass depth proved most influential on wear, with optimal values between 0.8 and 1.2 mm. Surface finish, assessed through mean roughness Ra, showed high dependence on pass depth, improving for low ap values and relatively high Vc values. These findings demonstrate that inserts fabricated via material extrusion can operate within a technological range like commercial inserts, presenting an advanced approach for customizing design and manufacturing while surpassing conventional insert limitations.
Keywords: Acero inoxidable - Fabricación; Impresión 3D; Cutting inserts; Material extrusion; FFF technology; Metal 3D printing; Tool wear